2023
DOI: 10.1007/s10603-022-09533-4
|View full text |Cite
|
Sign up to set email alerts
|

Sales of Electronic Nicotine Delivery Systems (ENDS) and Cigarette Sales in the USA: A Trend Break Analysis

Abstract: Electronic nicotine delivery systems (ENDS) are a potentially lower-risk tobacco product which could help smokers switch completely away from cigarettes. However, the lack of strong evidence to date of a measurable, population-level effect on reducing smoking has generated skepticism about ENDS’ potential benefits. This study examines whether increased US ENDS sales have been associated with reduced cigarette sales. Retail data on weekly per-capita cigarette and ENDS purchases in the USA during 2014–2019 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…These lower-than-expected smoking prevalences, correlated with e-cigarette use, suggest population-level displacement of cigarettes by e-cigarettes, consistent with extant modelling literature [28,29]. A significant overall decline in adult cigarette smoking is observed, above what was otherwise expected, even for younger adults, among whom the reported 'gateway' effect is claimed to be strong and e-cigarette use is relatively high [1].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These lower-than-expected smoking prevalences, correlated with e-cigarette use, suggest population-level displacement of cigarettes by e-cigarettes, consistent with extant modelling literature [28,29]. A significant overall decline in adult cigarette smoking is observed, above what was otherwise expected, even for younger adults, among whom the reported 'gateway' effect is claimed to be strong and e-cigarette use is relatively high [1].…”
Section: Discussionsupporting
confidence: 78%
“…Another useful approach to determining the overall impact of e-cigarette use on smoking prevalence (i.e., the combination of gateway and substitution effects) at the population level is to model expected trends in smoking prevalence, and then assess whether the introduction of e-cigarettes was associated with a net deviation from the expected smoking prevalence, either an increase (gateway) or decrease (substitution). Such modeling studies have generally found that the introduction of e-cigarettes was associated with more rapid declines in smoking prevalence [9,[26][27][28][29]. The present study uses this approach to assess whether and how much the introduction of e-cigarettes in the US may be correlated with declining smoking prevalence among adults in the following ways.…”
Section: Introductionmentioning
confidence: 97%
“…These exclusions omit a large share of tobacco sales. For instance, Selya et al (2023) conclude that about 50% of the e-cigarette market is not recorded by IRI. Analyses with the PATH data, in terms of where users purchase their e-cigarette products, show that about 60% of youth purchases of vaping products occur through tobacco specialty stores; the corresponding shares for young adults and adults are 70.24% and 67.26%, respectively.…”
Section: C Prior Studiesmentioning
confidence: 99%
“…Since their introduction to the U.S. market in the 2000s, electronic nicotine delivery systems (ENDS; Bandi et al, 2023;Brouwer et al, 2023;Romeh et al, 2023;Selya et al, 2023), a diverse class of products intended to deliver aerosolized nicotine to people who use them, have experienced considerable uptake. Between 2016 and 2019, ENDS sales increased roughly 300% in the United States (Ali et al, 2020).…”
mentioning
confidence: 99%